When x=-2, the value of y is
13 answers
The value of y when x = -2 is not provided in the given information.
Solve the equation for y. Then find the value of y for each value of x.
y+3x=5;x=-2,0,4
When x=-2, the value of y is
y+3x=5;x=-2,0,4
When x=-2, the value of y is
To find the value of y when x = -2, we can substitute the given value into the equation:
y + 3(-2) = 5
Simplifying, we have:
y - 6 = 5
Adding 6 to both sides of the equation:
y = 11
Therefore, when x = -2, the value of y is 11.
y + 3(-2) = 5
Simplifying, we have:
y - 6 = 5
Adding 6 to both sides of the equation:
y = 11
Therefore, when x = -2, the value of y is 11.
When x=0, the value of y is
To find the value of y when x = 0, substitute the given value into the equation:
y + 3(0) = 5
Simplifying, we have:
y + 0 = 5
y = 5
Therefore, when x = 0, the value of y is 5.
y + 3(0) = 5
Simplifying, we have:
y + 0 = 5
y = 5
Therefore, when x = 0, the value of y is 5.
When x=4, the value of y is
To find the value of y when x = 4, substitute the given value into the equation:
y + 3(4) = 5
Simplifying, we have:
y + 12 = 5
Subtracting 12 from both sides of the equation:
y = 5 - 12
y = -7
Therefore, when x = 4, the value of y is -7.
y + 3(4) = 5
Simplifying, we have:
y + 12 = 5
Subtracting 12 from both sides of the equation:
y = 5 - 12
y = -7
Therefore, when x = 4, the value of y is -7.
Solve the equation for u.
up+uv=t
up+uv=t
To solve the equation for u, we need to isolate the variable u on one side of the equation.
Starting with the equation: up + uv = t
We can factor out the common factor of u:
u(p+v) = t
Then, divide both sides of the equation by (p+v):
u = t / (p+v)
Therefore, the equation solved for u is u = t / (p+v).
Starting with the equation: up + uv = t
We can factor out the common factor of u:
u(p+v) = t
Then, divide both sides of the equation by (p+v):
u = t / (p+v)
Therefore, the equation solved for u is u = t / (p+v).
Solve the equation for y. Then find the value of y for each value of x.
3x-7y=19;x=-1,0,1
3x-7y=19;x=-1,0,1
To solve the equation for y, rearrange the equation:
3x - 7y = 19
Subtract 3x from both sides:
-7y = -3x + 19
Divide both sides by -7:
y = (3x - 19)/7
Now we can substitute the given values of x to find the corresponding values of y.
When x = -1:
y = (3*(-1) - 19)/7
y = (-3 - 19)/7
y = -22/7
y = -3.14 (rounded to two decimal places)
When x = 0:
y = (3*(0) - 19)/7
y = (-19)/7
y = -2.71 (rounded to two decimal places)
When x = 1:
y = (3*(1) - 19)/7
y = (-16)/7
y = -2.29 (rounded to two decimal places)
Therefore, for x = -1, the value of y is approximately -3.14.
For x = 0, the value of y is approximately -2.71.
For x = 1, the value of y is approximately -2.29.
3x - 7y = 19
Subtract 3x from both sides:
-7y = -3x + 19
Divide both sides by -7:
y = (3x - 19)/7
Now we can substitute the given values of x to find the corresponding values of y.
When x = -1:
y = (3*(-1) - 19)/7
y = (-3 - 19)/7
y = -22/7
y = -3.14 (rounded to two decimal places)
When x = 0:
y = (3*(0) - 19)/7
y = (-19)/7
y = -2.71 (rounded to two decimal places)
When x = 1:
y = (3*(1) - 19)/7
y = (-16)/7
y = -2.29 (rounded to two decimal places)
Therefore, for x = -1, the value of y is approximately -3.14.
For x = 0, the value of y is approximately -2.71.
For x = 1, the value of y is approximately -2.29.
When x,=-1 the value of y is
To find the value of y when x = -1, we can substitute the given value into the equation:
y = (3x - 19)/7
Substituting x = -1:
y = (3(-1) - 19)/7
Simplifying:
y = (-3 - 19)/7
y = (-22)/7
Therefore, when x = -1, the value of y is approximately -3.14 (rounded to two decimal places).
y = (3x - 19)/7
Substituting x = -1:
y = (3(-1) - 19)/7
Simplifying:
y = (-3 - 19)/7
y = (-22)/7
Therefore, when x = -1, the value of y is approximately -3.14 (rounded to two decimal places).